Hounsfield unit correlates with intervertebral disc degeneration in premenopausal and menopausal women: a radiological study - Ze Gao; Liangwei Zhao; Xiaoming Tian; Zhaohui Li; Haiyun Niu; Sidong Yang; Zhiyong Hou (Journal of Orthopaedic Surgery and Research)
Abstract Objectives This study aims to investigate whether Hounsfield unit (HU) value is correlated with intervertebral disc (IVD) degeneration (IVDD) by comparing premenopausal with menopausal women patients. Methods A total of 101 female patients who underwent treatment in our hospital between February 2022 and February 2023 were retrospectively reviewed and included in this study. All patients were divided into either the premenopausal group or the menopausal group, according to age and menopause status. The changes in disc height index (DHI) on X-ray, the Hounsfield unit (HU) value on computed tomography (CT), and the area of the nucleus pulposus (NP) on magnetic resonance imaging (MRI) were assessed and compared between the two groups. Results There is a significant difference in the Pfirrmann grading of T12-S1 discs between the premenopausal and menopausal groups; the menopausal group has more degenerated discs compared with the premenopausal group (P < 0.001). There is no significant difference in DHI measurements between the premenopausal and menopausal groups. HU values in the premenopausal group are greater compared with the menopausal group from T12 to S1 vertebrae (all P < 0.001). Regarding the NP area on MRI, the L2-L3 IV disc space have a bigger area in the premenopausal group compared with the menopausal group (P = 0.029), with no significant difference in other IVD segments. Conclusions The HU value on CT is significantly decreased with IVDD progression after menopause. The change in HU value could indirectly reflect vertebral bone mineral density. Therefore, the decline of estrogen after menopause leads to vertebral osteoporosis, which might contribute to IVDD progression.